The Complete Guide to Wines and Wine Drinking - Walton, Stuart (London, United Kingdom : Southwater, 2004)
This is a comprehensive, authorative and accesible guide to wine. Vivid colour photography and carefully illustrated maps offer a visual explanation of how the world of wine is developing day by day.
Technical basics -- Grape varieties -- France -- Europe, Africa, and The East -- Americas and the rest of the world.
Includes index.
Keywords: WINW AND WINE MAKING